Pew used by Mother Teresa - Ghosh, Ayan (2023)
Another famous visitor to the St. Thomas Cathedral was Mother Teresa (1910-1997), who attended prayer services at the church on 8th January 1983. A commemorative plaque is now placed on the pew (a long bench, seat, or enclosed box) used by her on the occasion, now placed at the front of the congregation.